2022
DOI: 10.1111/irv.13030
|View full text |Cite
|
Sign up to set email alerts
|

Pronounced antibody elevation after SARS‐CoV‐2 BNT162b2 mRNA booster vaccination in nursing home residents

Abstract: Background Infection control during COVID‐19 outbreaks in nursing facilities is a critical public health issue. Antibody responses before and after the third (booster) dose of SARS‐CoV‐2 vaccination in nursing home residents have not been fully characterized. Methods This study included 117 individuals: 54 nursing home residents (mean age, 83.8 years; 39 SARS‐CoV‐2‐naive and 15 previously infected) and 63 healthcare workers (mean age, 45.8 years; 32 SARS‐CoV‐2‐naive and 31 previously infected). Anti‐spike (rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 21 publications
2
14
0
Order By: Relevance
“…The NTs after the second and third doses were highest against the Wuhan strain, followed by the Alpha, Delta and Omicron BA.1, and BA.5 variants, indicating immune evasion by SARS-CoV-2 variants from the herd immunity raised by three doses of mRNA-based COVID-19 vaccine [9] , [10] , [11] . Our results showing that a third dose of mRNA vaccine elicited an enhanced immune response in RBD IgG and NTs against variant strains, including the Omicron BA.1 variant, are consistent with the results of previous studies in healthcare workers [20] , [21] , [22] and nursing home residents [23] , [24] . In this study, we also found that a third dose of mRNA vaccine induced an enhanced NT against Omicron BA.5 which was comparable to those against BA.1.…”
Section: Discussionsupporting
confidence: 92%
“…The NTs after the second and third doses were highest against the Wuhan strain, followed by the Alpha, Delta and Omicron BA.1, and BA.5 variants, indicating immune evasion by SARS-CoV-2 variants from the herd immunity raised by three doses of mRNA-based COVID-19 vaccine [9] , [10] , [11] . Our results showing that a third dose of mRNA vaccine elicited an enhanced immune response in RBD IgG and NTs against variant strains, including the Omicron BA.1 variant, are consistent with the results of previous studies in healthcare workers [20] , [21] , [22] and nursing home residents [23] , [24] . In this study, we also found that a third dose of mRNA vaccine induced an enhanced NT against Omicron BA.5 which was comparable to those against BA.1.…”
Section: Discussionsupporting
confidence: 92%
“…The definite antibody response induced by the fourth (second booster) vaccination in SARS‐CoV‐2‐naive residents is noteworthy. Our previous study showed a robust increase in antibody levels after the third dose in these residents 8 . These findings provide evidence that the ability to induce a sufficient antibody response persists in SARS‐CoV‐2‐naive residents, even after the fourth dose.…”
Section: Discussionsupporting
confidence: 61%
“…HCW, healthcare worker; IgG, immunoglobulin G; mRNA, messenger RNA; NHR, nursing home resident; RBD, receptor-binding domain; SARS-CoV-2, severe acute respiratory syndrome coronavirus 2 third dose was much higher than after the second dose, even 6 months after vaccination, because the antibody levels increased approximately five times after the third dose compared with the levels after the second dose. 8 This finding might have contributed to protection against infection. The definite antibody response induced by the fourth (second booster) vaccination in SARS-CoV-2-naive residents is noteworthy.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies on the effectiveness of the third dose of the vaccine found improved efficacy against SARS-CoV-2 infection and a reduction in hospitalization [ [8] , [9] , [10] , [11] , [12] , [13] , [14] ]. However, most studies on the effect of the third vaccination have been limited to a relatively short period of time after the third dose, and few longitudinal analyses of the effects of the third vaccination with an anti–SARS-CoV-2 vaccine have been reported.…”
Section: Introductionmentioning
confidence: 99%